Poetry and “natural mysticism” in Sergei Bulgakov’s legacy - Daniil Cherepanov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2025)
This article suggests a new point of view on Archpriest Sergei Bulgakov’s sophiology. The concept of Sophia has often been described as an artificial element in Bulgakov’s views, its emergence has been explained by different “influences”, e.g. of Vladimir Solovyov, Gnosticism, rationalist philosophy etc. This article, on the contrary, argues that the concept of Sophia was Bulgakov’s solution to problems which essentially and integrally belonged to his worldview. The article seeks to demonstrate that Bulgakov was a bearer of poetic tradition closely related to European and Russian Romanticism. This is corroborated by a comparison between Bulgakov’s work and works of fiction from the late 18th–early 19th centuries. It is further shown that this literary tradition was closely related to what Bulgakov called “natural mysticism”. A characteristic trait of such mysticism was the inclination to see some higher, feminine element permeating the entire nature. After his return to the Orthodox Church, Bulgakov strived to elaborate a comprehensive Christian worldview, which would include such poetic feelings, dreams and intuitions. Therefore, Bulgakov had to face a problem: he still had a good opinion of “natural mysticism”, perceiving the higher regions to which it provided access as part of the world blessed by the Creator, but he also understood that the feminine being, which his fellow poets saw in the depths of nature, was by no means Jesus Christ, Son of God. He tried to find a “Christian value” of this poetic worldview; the results, however, suffered from intrinsic conflicts. It is suggested that Bulgakov was at least partially aware of these conflicts and that his changing concept of Sophia resulted from attempts to overcome these inherent antinomies.